1998
DOI: 10.1177/153476569800400205
|View full text |Cite
|
Sign up to set email alerts
|

Victim characteristics and attributions of blame in male rape.

Abstract: Examined factors that may influence attributions of blame for male victims of rape. Whatley and Riggio (1993) found that victim arrest record and perceiver's belief in a just world influenced attributions of blame. The current study sought to replicate and extend these findings. Sexual orientation of the victim was manipulated along with arrest record, resulting in a 2 X 2 ANOVA. As expected, belief in a just world predicted greater victim blame and homosexual victims were accorded more blame than heterosexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Although proponents of the defensive attribution theory widely accept that victim blame results in decreased perceived victim similarity and vulnerability, in fact very little research has actually examined these outcomes (e.g., Amacker & Littleton, 2013). Moreover, several studies claim to support the defensive attribution theory without explicitly measuring the primary mechanisms, similarity and vulnerability (e.g., Daugherty & Esper, 1998; Finch & Munro, 2007; Hirschberger, 2006; Idisis et al, 2007; Kaplan & Miller, 1978; Yarmey, 1985). The current study sought to extend the breadth of defensive attribution literature by explicitly measuring these components to determine whether defensively attributed blame is actually effective at reducing perceived similarity and vulnerability as proposed by the theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although proponents of the defensive attribution theory widely accept that victim blame results in decreased perceived victim similarity and vulnerability, in fact very little research has actually examined these outcomes (e.g., Amacker & Littleton, 2013). Moreover, several studies claim to support the defensive attribution theory without explicitly measuring the primary mechanisms, similarity and vulnerability (e.g., Daugherty & Esper, 1998; Finch & Munro, 2007; Hirschberger, 2006; Idisis et al, 2007; Kaplan & Miller, 1978; Yarmey, 1985). The current study sought to extend the breadth of defensive attribution literature by explicitly measuring these components to determine whether defensively attributed blame is actually effective at reducing perceived similarity and vulnerability as proposed by the theory.…”
Section: Discussionmentioning
confidence: 99%
“…Decades ago, Walster (1966) conceptualized victim blame as a result of the defensive attribution theory, which posits that observers are motivated to blame victims to quell their own feelings of vulnerability to experiencing a similar tragedy. The theory has been referenced in over a dozen studies over the years aiming to understand the underlying mechanisms of attributions of responsibility and blame (Amacker & Littleton, 2013; Anderson, 1999; Burger, 1981; Burt & DeMello, 2002; Daugherty & Esper, 1998; Feldman, Ullman, & Dunkel-Schetter, 1998; Finch & Munro, 2007; Fulero & Delara, 1976; Gold, Landerman, & Bullock, 1977; Hirschberger, 2006; Idisis, Ben-David, & Ben-Nachum, 2007; Kaplan & Miller, 1978; Laufer & Gillespie, 2004; Libow & Doty, 1979; Muller, Caldwell, & Hunter, 1994; Olsen-Fulero & Fulero, 1997; Savage, Scarduzio, Harris, & Carlyle, 2017; Workman & Freeburg, 1999; Yarmey, 1985), though many of the aforementioned studies have evoked defensive attribution as a post hoc explanation for findings rather than measuring its components directly (Daugherty & Esper, 1998; Finch & Munro, 2007; Hirschberger, 2006; Idisis et al, 2007; Kaplan & Miller, 1978; Yarmey, 1985). By attributing blame, it is hypothesized that the observer can effectively distance themselves from the victim and feel protected from experiencing a similar tragedy, as the observer is reassured that they can avoid a similar attack by simply being different from the victim in some fundamental way.…”
Section: Introductionmentioning
confidence: 99%
“…2 In homophobic environments, homosexual survivors of rape may be seen as inviting rape by their very nature. 3,4 In around 70 countries, same-sex relations are criminalised and the taboo on homosexuality probably discourages all men who experience sexual torture from reporting it.…”
mentioning
confidence: 99%
“…Daugherty and Esper (1998) provide a nice replication and extension of the classic Whatley & Riggio (1993) study. The latter study they found that victims arrest record and belief in a just world accounted for why rape victims were more likely to be blamed than pitied.…”
Section: The Role Of Sexism and Homophobia On Attitudes Toward Rape V...mentioning
confidence: 93%
“…The investigators predicted and found that a substantial number of children in the program were exposed to considerable traumatic events and met the criteria for PTSD. The third paper by Daugherty and Esper (1998) reported the findings of an interesting study of reactions to male rape victims. Consistent with previous research, belief in a just world predicted greater victim blame and homosexual victims were accorded more blame than heterosexual victims.…”
mentioning
confidence: 99%